ISNAD CUM MATAN ANALYSIS SEBAGAI METODE OTENTIFIKASI HADIS NABI (ANALISIS PEMIKIRAN HADIS HARALD MOTZKI) - Umi Sumbulah; Zarwaki Zarwaki; Muhammad Miftakhul Huda (Jurnal Studi Hadis Nusantara, 2022)
The most important thing in studying the science of Hadith (Musthalah) is to testand determine the validity of Hadith. Because the hadith that will be used as atranscendental foundation in Islam, must be proven as authentic one. This articledescribes the theories of hadith authenticity argued by Harald Motzki namelysanad cum matan analysis. This theory of isnad cum matan analysis is a method insearching for the history of hadith by combining isnad and matan aspects. This studyuses the library or normative method with a literature study approach. The thesisput forward by Motzki can be used as an additional reference that complementsvarious classical theories implemented by moslem mutaqaddimin scholars. In otherwords, Motzki's theory can strengthen the argument of the authenticity of hadithconstructed by most of moslem scholars